UNIVERSITY TEACHER: METHODOLOGIST, RESEACHER, NOVATOR? - Svetlana I. Pozdeeva (Высшее образование в России)
The article focuses on changing activity of a modern university teacher mastering different professional models (Master, Bachelor and Academic) and diverse joint teacher-student activity models (Authoritarian, Leadership, Partnership). The connection between professional activity models and interactive models is pointed out. Besides, a special attention is paid to the influence of active methods in education on a teacher position in this activity from head to leader and partner. The author comes to a conclusion that teacher's activities is significantly based on co-organizing of various models, positions and roles.